In Vitro Antibacterial Activity of Waste Palm Cooking Oil Against Staphylococcus Aureus - Fiqih Faizara Ustadi; Agung Dwi Wahyu Widodo; Yuani Setiawati (Institute of Medico-legal Publications Pvt Ltd, 2022)
Background: Staphylococcus aureus is a Gram-positive coccus which acts as a pathogen causing awide range of infectious diseases. In recent years, several strains of S. aureus have been found to showresistance to several antibiotics. Waste cooking oil may be considered as an alternative antibacterialproduct, as it contains long-chain fatty acids whose antibacterial effectiveness against S. aureus hasbeen known for years. In addition, oxidative biocides produced during the frying process have manytargets for antibacterial activity in the cell and affect almost every biomolecule. Nonetheless, there isno literature that is able to prove the antimicrobial effects of the waste palm cooking oil. Objective: Toexamine the in vitro antibacterial effect of waste palm cooking oil against S. aureus. Method: a twofoldserial dilution method to set the minimum level of both inhibitory and bactericidal concentrations.Conclusion: This study showed that waste palm cooking oil did not show antibacterial effects againstS. aureus, indicating that waste palm cooking oil is not possibly to be applied as an antibacterial agentagainst S. aureus.